2000
DOI: 10.1108/02634500010308530
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of market intelligence to tactical and strategic business decisions

Abstract: One of the drivers of both strategy and success in the marketplace is the role of market intelligence. Samples a broad cross section of firms regarding their level of MI activity; MI data sources and MI accountability. Regarding MI activity and its value to consumer/competitive intelligence, two‐thirds of the companies indicated a dramatic increase in level of activity and nearly three‐fifths (54 per cent) said the impact of MI contributes heavily to tactical and strategic decision making. One third said activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
8

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 5 publications
4
34
0
8
Order By: Relevance
“…Although CI is assumed to be a strategic activity, both in Flanders (62.9 per cent) and in South Africa (55.6 per cent) in the majority of the cases CI is practiced in the marketing and sales department. This difference between the two countries is not statistically significant ðx 2 ¼ 0:985; p ¼ 0:321Þ: This is in line with the results reported by Lackman et al (2000). Furthermore, Trim (2004) even argues that it is advisable to integrate CI work with marketing intelligence work.…”
Section: How CI Is Conductedsupporting
confidence: 90%
See 1 more Smart Citation
“…Although CI is assumed to be a strategic activity, both in Flanders (62.9 per cent) and in South Africa (55.6 per cent) in the majority of the cases CI is practiced in the marketing and sales department. This difference between the two countries is not statistically significant ðx 2 ¼ 0:985; p ¼ 0:321Þ: This is in line with the results reported by Lackman et al (2000). Furthermore, Trim (2004) even argues that it is advisable to integrate CI work with marketing intelligence work.…”
Section: How CI Is Conductedsupporting
confidence: 90%
“…A similar picture emerges with respect to part-time staff ðx 2 ¼ 53:981; p , 0:001Þ: This is much lower than the percentages reported by Lackman et al (2000) in their In Flanders, the top management level is significantly more responsible for CI-activity than in South Africa (64.5 versus 49.3 per cent), in which other departments more often take the lead ðx 2 ¼ 13:086; p , 0:001Þ ( Figure 6). This importance of senior and top management was also highlighted by Wright et al (2002) in their in-depth study of a CI-typology of UK firms.…”
Section: How CI Is Conductedsupporting
confidence: 73%
“…Lackman, Saban and Lanasa (2000) examined the value of MI to tactical and strategic planning, and found it to be generally useful to planning processes in the organisation. Their research also indicated that customers, manufacturers and R & D departments are the most important internal sources of information, while client meetings are by far the most important sources of external information.…”
Section: Marketing Intelligence and Strategic Marketingmentioning
confidence: 99%
“…The literature review undertaken as part of the research reported here uncovered only two such studies. Lackman, Saban and Lanasa (2000) conducted descriptive research on the relationship between MI and strategic marketing. However, this study did not address the relative complexity of MI, and focused on it as one broad concept instead of a complex and interrelating set of subsystems and activities.…”
Section: Introductionmentioning
confidence: 99%
“…Among other things, this could help an organisation to determine a clear strategic direction 1 recognise warning signals and avoid surprises 2 and generally shape current decisions that might impact on future operations. 3 Further advantages of remaining ahead of the game, according to Simkin, include 'serving the ''best'' customers, minimising threats, maximising returns and using resources to the greatest advantage'.…”
Section: Respondents In 70 Advertising Agencies 70 Public Relations mentioning
confidence: 99%